2015
DOI: 10.1021/acs.energyfuels.5b02032
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation of Solid Recovered Fuel (SRF) Gasification: Effect of Temperature and Equivalence Ratio on Process Performance and Release of Minor Contaminants

Abstract: The growing problem related to municipal solid waste generation has encouraged the development of alternative paths to convert waste to energy. Among the different options, gasification has been proposed as an interesting and efficient technology. In this study the influence of equivalence ratio (ER) and temperature on the performance of the air-gasification process during the gasification of a SRF material has been evaluated. One of the parameters to assess the gasification performance was the tracking of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 43 publications
(109 reference statements)
7
31
0
Order By: Relevance
“…In the past few years, SRFs gasification was increasingly studied in lab-scale fluidized beds, and the effect of the operating conditions on gasification behavior was investigated. Increasing equivalence ratio (ER) was proved to promote the oxidation reactions which increases both the syngas yield and the carbon conversion [26,27]. Similar results were obtained with the gasification of other wastes [10,28].…”
Section: Different Gasification Technologies Have Been Developed Amosupporting
confidence: 59%
See 3 more Smart Citations
“…In the past few years, SRFs gasification was increasingly studied in lab-scale fluidized beds, and the effect of the operating conditions on gasification behavior was investigated. Increasing equivalence ratio (ER) was proved to promote the oxidation reactions which increases both the syngas yield and the carbon conversion [26,27]. Similar results were obtained with the gasification of other wastes [10,28].…”
Section: Different Gasification Technologies Have Been Developed Amosupporting
confidence: 59%
“…Contradictory results were reported about the evolution of the CH4 content and of the LHV of the syngas. While Berrueco et al found that they reached a maximum at 800 °C before to decrease with higher temperature [26,27], Dunnu et al reported that they increased with rising temperature from 800 to 850 °C [21]. These opposite trends can result from the different SRF composition, but a lack of study devoted to the influence of the SRF composition prevents to conclude this point.…”
Section: Different Gasification Technologies Have Been Developed Amomentioning
confidence: 97%
See 2 more Smart Citations
“…Biomass gas generated by means of gasification from organic materials, such as agricultural and forestry residues, which exist abundantly in rural places, might be one potential solution to the problem of central gas supply [1]. However, due to assorted biomass resources, as well as gasification conditions and agents [2][3][4][5][6], the H 2 /CO ratio of acquired biomass gas varies greatly, and particularly, low H 2 /CO ratio biomass gas (H 2 /CO < 1) cannot be applied directly by urban residents because of its dreadful toxicity and relatively low heating value. Hence, from the standpoint of safety and efficiency, a series of requisite processing technologies has to be employed in order to eliminate the above two drawbacks before it is transported through a pipeline to downstream users.…”
Section: Introductionmentioning
confidence: 99%